Archaeological Perspectives on Indiana Jones And Raiders: The Lost Ark - Siti - Nurmala; Salsa Solli Nafsika (Universitas Pendidikan Indonesia, 2021)
Indina Jones and The Raiders: The Lost Ark is a 1981 American action adventure film in which Harrison plays Indiana Jones, an archaeologist who travels the world competing with Nazi Germany in 1936 to find the Ark of the Covenant, which has long been lost. The research method used in this study is a qualitative approach and semiotic analysis of Charles Sanders Pierce. Sources of data obtained from this research are watching the movie Indiana Jones and The Raiders: The Lost Ark which is then selected visuals or images from scenes in the film that contain archaeological elements, as well as secondary data obtained from literature studies that can support primary data in this research. The purpose in writing this article is to analyze and discover the archaeological meaning in the film Indiana Jones and The Raiders: The Lost Ark. The data collection technique used in this study is an observation technique by analyzing and watching and observing carefully from each scene and dialogue in the film Indiana Jones and The Raiders: The Lost Ark, then recording and analyzing according to the research method used, namely by analyzing the scene. using the semiotic analysis of Charles Sander Pierce with categories of icons, indexes and symbols.